Dietary intake and risk of rheumatoid arthritis—a cross section multicenter study. Issue 12 (December 2016) - He, Jing; Wang, Yu; Feng, Min; Zhang, Xia; Jin, Yue-Bo; Li, Xue; Su, Lin-Chong; Liu, Shuang; Wang, Ai-Xue; Chen, Xiao-Mei; Wu, Li-Jun; Yu, Xiao-Xia; et al.
Abstract Environmental factors play an important role in the development of rheumatoid arthritis (RA). Among these factors, smoking is generally considered to be an established risk factor for RA. Data regarding the impact of diet on risk of RA development is limited. This study assessed the impact of dietary patterns on RA susceptibility in Chinese populations. This was a large scale, case-control study composed of 968 patients with RA and 1037 matched healthy controls. Subjects were recruited from 18 teaching hospitals. Socio-demographic characteristics and dietary intakes 5 years prior to the onset of RA were reported by a self-administered questionnaire. Differences in quantity of consumption between cases and controls were analyzed by Student'st test. Multiple logistic regression analysis was applied to identify independent dietary risk factor(s) responsible for RA susceptibility. Compared to healthy individuals, RA patients had decreased consumption of mushrooms (P  = 0.000), beans (P  = 0.006), citrus (P  = 0.000), poultry (P  = 0.000), fish (P  = 0.000), edible viscera (P  = 0.018), and dairy products (P  = 0.005). Multivariate analyses revealed that several dietary items may have protective effects on RA development, such as mushrooms (aOR = 0.669; 95%CI = 0.518–0.864, P  = 0.002), citrus fruits (aOR = 0.990; 95%CI = 0.981–0.999, P  = 0.04), and dairy products (aOR = 0.921; 95%CI 0.867–0.977, P  = 0.006). Several dietary factors had independent effects on RA susceptibility. Dietary interventions may reduce the risk of RA.